Micropropagation of Dendrocalamus brandisii Kurz. Using In-vivo Nodal Explants - Mukunthakumar, S.; Mathur, Jaideep; Nair, P. K. K.; Mathur, S. N. (Indian Forester, 1999)
Bamboo is an important woody grass which have found multitudinous uses. This paper describes the methods of continuous supply of propagating materials through in-vitro culture of Dendrocalamus brandisii by using in-vivo nodal segments. Nodal segments produced multiple shoots on a modified MS medium supplemented with 5.0 mg/l BAP. Rooting was achieved in clumps after dipping in IBA solution for 24 hours and subsequently transferring them to the basal medium. Plantlets were transferred to field conditions following hardening of 10-15 days.